GE_GERICHTE P/5545/2023 vom 20. Oktober 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;GESTION DÉLOYALE;DÉLAI;PLAINTE PÉNALE;GÉRANT(SENS GÉNÉRAL);DOMMAGE;LÉSÉ | CPP.310; CP.31; CP.158